The Effect of Exercise on Reducing Dysmenorrhea in Nursing Students - Andry Sartika; Pusma Kartini (PT Bukuloka Literasi Bangsa, 2025)
Introduction: Menstrual pain (dysmenorrhea) is caused by an imbalance of progesterone hormones in the blood, resulting in pain. Psychological factors also play a role in the occurrence of dysmenorrhea in some women. The purpose of this study was to determine the effect of dysmenorrhea exercises in reducing menstrual pain in female students during menstruation. Method: This study was conducted using a quasi-experimental design in one group (one group pre-test-post-test design). Sampling was done using purposive sampling. The sample in this study consisted of 15 people. Results: The research results were analyzed using a T-test, namely a paired simple T-test, because the distribution was normal. The results showed a t-value of 8.951 with a significance value of the Paired Sample t-test of 0.000, which was smaller than the error rate (α) of 0.05. Conclusion: There is an effect of dysmenorrhea exercises in reducing dysmenorrhea. Future researchers are expected to better control factors that can affect the degree of dysmenorrhea, such as psychological factors, constitutional factors, and activity, and to perform dysmenorrhea exercises every morning or evening so that the results of reducing the degree of dysmenorrhea can be maximized. Keywords: Menstrual Cramps Exercise, Menstrual Cramps.